2005
DOI: 10.1177/107179190501100205
|View full text |Cite
|
Sign up to set email alerts
|

Keeping it "All in the Family:" Does Nepotism in the Hiring Process Really Benefit the Beneficiary?

Abstract: The purpose of this research was to examine the consequences of being perceived as having benefited from a family connection during the hiring process. One hundred and ninety-seven upper-level undergraduate students reviewed materials describing three candidates for a managerial position. Selection method (merit vs. nepotism) and gender of the person who received the position were manipulated in the materials. Results revealed that not only was nepotism perceived as being less fair than merit-based hiring, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 13 publications
2
69
0
3
Order By: Relevance
“…This study demonstrated that potential applicants evaluate organizations based on their nepotistic practices, create fairness judgments about the organization and have significant reactions against the organization. These results extend the previous research of Padgett and Morris (2005), by focusing on the impact nepotism may have on the organization as a whole. Their study primarily pertained to the impact of nepotism on the nepotistic relation.…”
Section: Limitation Future Directions and Implicationssupporting
confidence: 72%
See 4 more Smart Citations
“…This study demonstrated that potential applicants evaluate organizations based on their nepotistic practices, create fairness judgments about the organization and have significant reactions against the organization. These results extend the previous research of Padgett and Morris (2005), by focusing on the impact nepotism may have on the organization as a whole. Their study primarily pertained to the impact of nepotism on the nepotistic relation.…”
Section: Limitation Future Directions and Implicationssupporting
confidence: 72%
“…Their study primarily pertained to the impact of nepotism on the nepotistic relation. This paper extended the previous research on nepotism by elucidating the psychological mechanism of organizational justice, while the previous studies considered fairness as outcome variable of importance (Chao, Ya-Ru & Xin, 2004;Padgett & Morris, 2005), this study framed fairness as the major component to how nepotism is evaluated. While the results were not in the intended direction, this study was the first to truly consider the impact the self-concept may have on these evaluations and to suggest that how we relate to others is of particular importance in our consideration of nepotism.…”
Section: Limitation Future Directions and Implicationsmentioning
confidence: 89%
See 3 more Smart Citations